Wellbeing in Urban Greenery: The Role of Naturalness and Place Identity - Knez, Igor; Ode Sang, Åsa; Gunnarsson, Bengt; Hedblom, Marcus (Frontiers in Psychology, 2018)
The aim was to investigate effects of urban greenery (high vs. low naturalness) on place identity and wellbeing, and the links between place identity and wellbeing. It was shown that participants (Gothenburg, Sweden, N = 1347) estimated a stronger attachment/closeness/belonging (emotional component of place-identity), and more remembrance and thinking about and mental travel (cognitive component of place-identity) in relation to high vs. low perceived naturalness. High naturalness was also reported to generate higher wellbeing in participants than low naturalness. Furthermore, place identity was shown to predict participants’ wellbeing in urban greenery, accounting for 35% of variance explained by the regression. However, there was a stronger relationship between the emotional vs. the cognitive component of place identity and wellbeing. Finally, a significant role of place identity in mediating the naturalness-wellbeing relationship was shown, indicating that the naturalness-wellbeing connection can be partly accounted for by the psychological mechanisms of people-place bonding.